1996
DOI: 10.1364/ao.35.001056
|View full text |Cite
|
Sign up to set email alerts
|

National Institute of Standards and Technology high-accuracy cryogenic radiometer

Abstract: A high-accuracy cryogenic radiometer has been developed at the National Institute of Standards and Technology to serve as a primary standard for optical power measurements. This instrument is an electrical-substitution radiometer that can be operated at cryogenic temperatures to achieve a relative standard uncertainty of 0.021% at an optical power level of 0.8 mW. The construction and operation of the high-accuracy cryogenic radiometer and the uncertainties in optical power measurements are detailed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 12 publications
1
97
0
3
Order By: Relevance
“…The NIST standard photometers are composed of a silicon photodiode, a (l )-correction lter and a high-precision aperture, and are also equipped with a temperature sensor that allows for a correction for change in photometer temperature. The absolute spectral responsivity (A/W) of the photometers is calibrated annually by the NIST Spectral Response Calibration Facility [6], traceable to the NIST absolute cryogenic radiometer [7]. With the calibrated aperture area and a correction for spatial non-uniformity of response over the aperture, the illuminance responsivity (A/lx) of each photometer for 2856 K Planckian radiation is determined.…”
Section: The Nistmentioning
confidence: 99%
“…The NIST standard photometers are composed of a silicon photodiode, a (l )-correction lter and a high-precision aperture, and are also equipped with a temperature sensor that allows for a correction for change in photometer temperature. The absolute spectral responsivity (A/W) of the photometers is calibrated annually by the NIST Spectral Response Calibration Facility [6], traceable to the NIST absolute cryogenic radiometer [7]. With the calibrated aperture area and a correction for spatial non-uniformity of response over the aperture, the illuminance responsivity (A/lx) of each photometer for 2856 K Planckian radiation is determined.…”
Section: The Nistmentioning
confidence: 99%
“…The basic theory of standard detector calibration method is that the responsivity of untested sensor can be acquired when the two device receive the same incident optical radiation. Because the responsivity of standard detector is known, the untested sensor calibration result can be obtained easily with substitution method [20] .…”
Section: The Untested Spectrometer Responsivity Calibrated With Standmentioning
confidence: 99%
“…The Irradiance responsivity calibration instrument using standard light calibration method According to the Ep. (20), the uncertainty becomes:…”
Section: Irradiance Responsivity Calibration Standard Light Calibratimentioning
confidence: 99%
“…The most significant change was to base the measurements on the NIST High Accuracy Cryogenic Radiometer [22]. At the time, the HACR was the U.S. primary standard for optical power.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement equation for the "substitution method with monitor" (Fig. 3.3 x-^x=^x-Gx-^bsx-^x-^x, (3.21) and = K,^^-"^= s^^• p^sx '^x "^x • (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) The ratio of these two signals is: Vis/NIR SCF using the 100 W quartz-halogen lamp and (b) UV SCF using the argon mini-arc as a source. The Optical Technology Division within NIST presently has two cryogenic radiometers that provide the basis for the spectral radiant power responsivity scale: the NIST-designed POWR (Figure 5.2), and the L-1 ACR [23] (Figure 5.3 intercomparison between POWR and the L-1 ACR showed that these two standards agreed to within 0.02 %, which is within their combined uncertainties as shown in Figure 5.4 [23].…”
Section: Introductionmentioning
confidence: 99%